Ion specific effects of sodium and potassium on the catalytic activity of HIV-1 protease - Heyda, Jan; Pokorná, Jana; Vrbka, Lubos; Vácha, Robert; Jagoda-Cwiklik, Barbara; Konvalinka, Jan; Jungwirth, Pavel; Vondrásek, Jirí (Physical chemistry chemical physics, 2009)
The behavior of HIV-1 protease in aqueous NaCl and KCl solutions is investigated by kinetic measurements and molecular dynamics simulations. Experiments show cation-specific effects on the enzymatic activity. The initial velocity of peptide substrate hydrolysis increases with salt concentration more dramatically in potassium than in sodium chloride solutions. Furthermore, significantly higher catalytic efficiencies (k(cat)/K(M)) are observed in the presence of K+ compared to Na+ at comparable salt concentrations. Molecular dynamics simulations provide insight into this ion-specific behavior. Sodium is attracted more strongly than potassium to the protein surface primarily due to stronger interactions with carboxylate side chain groups of aspartates and glutamates. These effects are of particular importance for acidic amino acid residues at or near the active site of the enzyme, including a pair of aspartates at the entrance to the reaction cavity. We infer that the presence of more Na+ than K+ at the active site leads to a lower increase in enzymatic activity with increasing salt concentration in the presence of Na+, likely due to the ability of the alkali cations at the active site to lower the efficiency of substrate binding.
Keywords: Ions; ionty; draslík; Molecular Dynamics Simulation; sodík; Potassium; Humans; HIV Protease; simulace molekulární dynamiky; HIV-proteasa; Sodium; lidé